A View on the Dialectic Between the Individual and the Environment - Mila Martínez (Coolabah, 2007)
The analysis of the relationship between the individual, their perception of the external world and their behaviour in it opens up the discussion of human agency and the dialectic of the individual and the social, and the individual and the environment. This essay will discuss this dialectic and will hint at possible ways to map the relationships between, on the one hand, Indigenous peoples and white Australia; and, on the other, between the rural and urban space which they inhabit and which, simultaneously, shape their identity as much as it is shaped by its inhabitants. It will also discuss how power and meaning are conditioned by subjectivity and space.